Limiting the Number of Potential Binding Modes by Introducing Symmetry into Ligands: Structure‐Based Design of Inhibitors for Trypsin‐Like Serine Proteases. Issue 2 (2nd December 2015) - Furtmann, Norbert; Häußler, Daniela; Scheidt, Tamara; Stirnberg, Marit; Steinmetzer, Torsten; Bajorath, Jürgen; Gütschow, Michael
Abstract: In the absence of X‐ray data, the exploration of compound binding modes continues to be a challenging task. For structure‐based design, specific features of active sites in different targets play a major role in rationalizing ligand binding characteristics. For example, dibasic compounds have been reported as potent inhibitors of various trypsin‐like serine proteases, the active sites of which contain several binding pockets that can be targeted by cationic moieties. This results in several possible orientations within the active site, complicating the binding mode prediction of such compounds by docking tools. Therefore, we introduced symmetry in bi‐ and tribasic compounds to reduce conformational space in docking calculations and to simplify binding mode selection by limiting the number of possible pocket occupations. Asymmetric bisbenzamidines were used as starting points for a multistage and structure‐guided optimization. A series of 24 final compounds with either two or three benzamidine substructures was ultimately synthesized and evaluated as inhibitors of five serine proteases, leading to potent symmetric inhibitors for the pharmaceutical drug targets matriptase, matriptase‐2, thrombin and factor Xa. This study underlines the relevance of ligand symmetry for chemical biology. Abstract : Ready to dock : The exploration of compound binding modes continues to be a challenging task. Here, symmetry was introduced in bi‐ and tribasic compounds to reduce conformational space in docking calculations and to simplify binding mode selection by limiting the number of possible pocket occupations. Bisbenzamidines were used as starting points for a multistage and structure‐guided optimization leading to branched inhibitors for trypsin‐like serine proteases (see figure).